H-BN-containing magnetic adsorbent and preparation method and application thereof
By developing the magnetic adsorbent Fe3O4@h-BN@SiO2@PDA containing h-BN, the magnetic solid phase extraction technology is used to solve the problem of difficult to quickly and selectively detect quinolones in the existing technology, and efficient and environmentally friendly sample pretreatment and adsorption effects are achieved.
Patent Information
- Application Number
- CN202510136403.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to detect quinolones antibiotics quickly and selectively, and commonly used pretreatment methods require a large number of organic solvents and time-consuming extraction and purification processes.
A magnetic adsorbent containing h-BN was developed, and a composite material of Fe3O4@h-BN@SiO2@PDA was used to achieve high selective adsorption of quinolones antibiotics using magnetic solid phase extraction technology.
It achieves high selectivity and good adsorption effect on quinolones antibiotics, simplifies the sample pretreatment process, reduces dependence on organic solvents, and is suitable for industrial production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a magnetic adsorbent containing h-BN and a preparation method and application thereof. Background Art
[0002] Quinolones are widely used to treat animal diseases. Due to the residues of quinolones in animal tissues, quinolone antibiotics remain in the human body after humans eat animal tissues, causing serious drug resistance to the drugs in human diseases, affecting the treatment of human diseases. Therefore, there is an urgent need to develop sensitive and reliable methods for rapid and selective detection of quinolone antibiotics to protect public health.
[0003] The complex matrix of food samples often causes significant interference during the analysis process, thus affecting the detection accuracy. Therefore, it is crucial to determine the appropriate sample pretreatment method. Common pretreatment methods include liquid-liquid extraction (LLE), protein precipitation, solid phase extraction (SPE) and solid phase microextraction (SPME). However, these techniques usually require the use of large amounts of organic solvents and involve time-consuming extraction and purification processes. In recent years, compared with traditional pretreatment methods, magnetic solid phase extraction (MSPE) has been widely used in the extraction of complex samples due to its simple operation, rapidity, reusability and environmental friendliness. This technology combines magnetic materials into adsorbents and uses external magnets to achieve rapid separation and extraction without additional centrifugation or filtration. The adsorbent is the core, and the type and characteristics of the adsorbent affect the selection and extraction performance of MSPE. CN118743980 A discloses a starch-based magnetic adsorbent for the adsorption of quinolone antibiotics in wastewater. Its preparation process is complicated and it is impossible to achieve selective adsorption of quinolone antibiotics.
[0004] Hexagonal boron nitride (h-BN) has low toxicity, good biocompatibility, high porosity, high specific surface area, high chemical stability, high antioxidant capacity, chemical inertness and low density, and has attracted extensive attention. However, its dispersibility in water is poor, and how to apply hexagonal boron nitride to the detection of antibiotics has become a new topic in the field of adsorption material technology.
[0005] Based on the above background, the present application discloses a magnetic adsorbent containing h-BN for extracting quinolone antibiotics in samples in MSPE. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a magnetic adsorbent containing h-BN and a preparation method and application thereof.
[0007] To solve the above problems, the technical solution adopted by the present invention is: Technical Theme 1 A magnetic adsorbent containing h-BN is prepared by the following steps: S1: Disperse h-BN and iron salt in water in turn, stir to dissolve the iron salt, add alkaline solution to adjust the pH to 10-11, and obtain a mixed solution; S2: stirring the mixed solution at 800-1000 rpm for 5-7 h at 80-90 °C, collecting the product with a magnet, washing, and drying to obtain a Fe3O4@h-BN composite material; S3: Disperse the Fe3O4@h-BN composite material in an ethanol solution, add an alkaline solution, adjust the pH to 8-8.5, drop tetraethoxysilane into the reaction system, react at 35-50 °C for 5-7 h, then add dopamine hydrochloride to the reaction system, stir at 400-500 rpm at room temperature for 1-3 h, separate the product with a magnet, wash and dry to obtain the magnetic adsorbent Fe3O4@h-BN@SiO2@PDA.
[0008] As a further improvement of the present invention, the iron salt is selected from ferrous chloride or ferrous sulfate; the alkaline solution is selected from ammonia water, sodium hydroxide solution or potassium hydroxide solution; and the ethanol solution is an ethanol solution with a volume ratio of ethanol to water of 4:1.
[0009] As a further improvement of the present invention, the mass molar ratio of h-BN in S1 to iron in the iron salt is 60 mg: 0.8-1.2 mmol.
[0010] As a further improvement of the present invention, in the reaction system described in S3, the dosage of Fe3O4@h-BN, tetraethoxysilane and dopamine hydrochloride is in the ratio of 150 mg: 0.2-0.3 mL: 120-150 mg.
[0011] As a further improvement of the present invention, the dosage of h-BN and water in S1 is 150 mg: 40-70 mL.
[0012] As a further improvement of the present invention, the dosage relationship of Fe3O4@h-BN and ethanol solution in S3 is 150 mg:40-70 mL.
[0013] As a further improvement of the present invention, the mass molar ratio of h-BN in S1 to iron in the iron salt is 60 mg:1 mmol.
[0014] In the reaction system described in S3, the dosage of Fe3O4@h-BN, tetraethoxysilane and dopamine hydrochloride is 150 mg: 0.25 mL: 135 mg.
[0015] As a further improvement of the present invention, the dosage relationship of h-BN and water in S1 is 150 mg:50 mL; The dosage relationship of Fe3O4@h-BN and ethanol solution in S3 is 150 mg:60 mL.
[0016] Technical Theme 2 A method for preparing a magnetic adsorbent containing h-BN as described in technical subject one.
[0017] Technical Theme 3 A use of a magnetic adsorbent containing h-BN as described in Technical Topic 1 in the detection of quinolone antibiotics.
[0018] The beneficial effects of adopting the above technical solution are: The magnetic adsorbent containing h-BN disclosed in the present application has high selectivity and good adsorption effect on quinolone antibiotics. 2 The hybrid structure has a good mutual adsorption effect on quinolone antibiotics. SiO2 and PDA modification on the Fe3O4@h-BN surface can further enhance the adsorption effect of the adsorbent on quinolone antibiotics.
[0019] The preparation method of the magnetic adsorbent disclosed in the present application is simple, the materials and reagents are easily available, the conditions are mild, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is the FT-IR graph of h-BN, Fe3O4 prepared in Comparative Example 1 of the present application, Fe3O4@h-BN prepared in Example 1 of the present application, Fe3O4@h-BN@SiO2 prepared in Comparative Example 2 of the present application, and Fe3O4@h-BN@SiO2@PDA prepared in Example 1 of the present application.
[0021] Figure 2 1 is a SEM image of the materials described in the examples of the present application. Figure a is h-BN; Figure b is Fe3O4@h-BN prepared in Example 1; Figure c is Fe3O4@h-BN@SiO2@PDA prepared in Example 1. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is clearly and completely described below in conjunction with specific embodiments.
[0023] In the specific implementation mode of this application: Hexagonal boron nitride (h-BN) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Standard substances ciprofloxacin hydrochloride (CIP), lomefloxacin hydrochloride (LOM), levofloxacin hydrochloride (OFL), and enrofloxacin (ENR) were purchased from Shanghai Dibai Biotechnology Co., Ltd. (Shanghai, China).
[0024] Example 1 S1: 150 mg h-BN was dispersed in 50 mL ultrapure water, and 0.695 g FeSO4·7H2O (2.5 mmol) was added to the above solution. After stirring for 10 min, ammonia water was added to adjust the pH of the solution to 11 to obtain a mixed solution. S2: The mixed solution was placed in a constant temperature water bath, stirred at 900 rpm for 6 hours at 90 °C, and then cooled to room temperature. The black dispersion was separated from the solution with a magnet and washed with ultrapure water and methanol until neutral. Finally, the sample was placed in a vacuum drying oven and dried at 60 °C for 10 h to obtain the Fe3O4@h-BN composite material.
[0025] S3: Disperse 150 mg Fe3O4@h-BN in 60 mL ethanol solution (ethanol: water 4:1, v / v). Then, add ammonia water to the mixed solvent and adjust the pH to 8.5. Ultrasonicate for 10 min, drop 0.25 mL tetraethoxysilane (TEOS) into the system, and let stand at 40 °C for 6 h. Then add 135 mg dopamine hydrochloride to the bottle, stir at 500 rpm for 2 h, separate the obtained product with an external magnetic field, and wash with water and ethanol. Dry under vacuum at 60 °C for 7 h. Fe3O4@h-BN@SiO2@PDA is obtained.
[0026] Example 2 S1: Disperse 150 mg h-BN in 40 mL ultrapure water, weigh 2 mmol ferrous chloride and add it to the above solution. After stirring for 10 min, add ammonia water to adjust the pH of the solution to 11 to obtain a mixed solution. S2: The mixed solution was placed in a constant temperature water bath, stirred continuously at 80 ℃ and 800 rpm for 5 hours, cooled to room temperature, and the black dispersion was separated from the solution with a magnet, and washed with ultrapure water and methanol until neutral. Finally, the sample was placed in a vacuum drying oven and dried at 60 ℃ for 10 h to obtain the Fe3O4@h-BN composite material.
[0027] S3: Disperse 150 mg Fe3O4@h-BN in 40 mL ethanol solution (ethanol: water 4:1, v / v). Then, add ammonia water to the mixed solvent and adjust the pH to 8.5. Ultrasonicate for 10 min, drop 0.20 mL tetraethoxysilane into the system, and let stand at 35 °C for 7 h. Then add 120 mg dopamine hydrochloride into the bottle, stir at 500 rpm for 1 h, separate the obtained product with an external magnetic field, and wash with water and ethanol. Dry under vacuum at 60 °C for 7 h. Fe3O4@h-BN@SiO2@PDA is obtained.
[0028] Example 3 S1: Disperse 150 mg h-BN in 70 mL ultrapure water, weigh 3 mmol FeSO4·7H2O and add it to the above solution. After stirring for 10 min, add ammonia water to adjust the pH of the solution to 11 to obtain a mixed solution. S2: The mixed solution was placed in a constant temperature water bath, stirred continuously at 90 °C and 1000 rpm for 7 hours, then cooled to room temperature, the black dispersion was separated from the solution with a magnet, and washed with ultrapure water and methanol until neutral. Finally, the sample was placed in a vacuum drying oven and dried at 60 °C for 10 h to obtain the Fe3O4@h-BN composite material.
[0029] S3: Disperse 150 mg Fe3O4@h-BN in 70 mL ethanol solution (ethanol: water 4:1, v / v). Then, add ammonia water to the mixed solvent and adjust the pH to 8.5. Ultrasonicate for 10 min, drop 0.3 mL tetraethoxysilane into the system, and let stand at 50 °C for 5 h. Then add 150 mg dopamine hydrochloride into the bottle, stir at 400 rpm for 3 h, separate the obtained product with an external magnetic field, and wash with water and ethanol. Dry under vacuum at 60 °C for 7 h. Fe3O4@h-BN@SiO2@PDA is obtained.
[0030] Comparative Example 1 Preparation of Fe3O4 Weigh 0.695 g FeSO4·7H2O and add it to 50 mL ultrapure water. After stirring for 10 min, add NH3·H2O to adjust the pH of the solution to 11. Place the solution in a constant temperature water bath and stir at 900 rpm for 6 hours at 90 °C. Then cool it to room temperature, separate the black dispersion from the solution with a magnet, and wash it with ultrapure water and methanol until it is neutral. Finally, place the sample in a vacuum drying oven and dry it at 60 °C for 10 h to obtain Fe3O4.
[0031] Comparative Example 2 Preparation of Fe3O4@h-BN@SiO2 150 mg of Fe3O4@h-BN prepared in Example 1 was dispersed in 60 mL of ethanol solution (ethanol: water 4:1, v / v). Then, ammonia water was added to the mixed solvent and the pH was adjusted to 8.5. Ultrasonication was performed for 10 min, and 0.25 mL of TEOS was dropped into the system and allowed to stand at 40 °C for 6 h. After stirring at 500 rpm for 2 h, the obtained product was separated by an external magnetic field and washed with water and ethanol. It was dried under vacuum at 60 °C for 7 h to obtain Fe3O4@h-BN@SiO2.
[0032] Comparative Example 3 Preparation of Fe3O4@SiO2@PDA 150 mg of Fe3O4 prepared in Comparative Example 1 was dispersed in 60 mL of ethanol solution (ethanol: water 4:1, v / v). Then, ammonia water was added to the mixed solvent and the pH was adjusted to 8.5. Ultrasonication was performed for 10 min, and 0.25 mL of TEOS was dropped into the system and allowed to stand at 40 °C for 6 h. Then, 135 mg of dopamine hydrochloride was added, stirred at 500 rpm for 2 h, and the obtained product was separated by an external magnetic field and washed with water and ethanol. Fe3O4@SiO2@PDA was obtained by vacuum drying at 60 °C for 7 h.
[0033] Comparative Example 4 Preparation of Fe3O4@h-BN@PDA The Fe3O4@h-BN (150 mg) prepared in Example 1 was dispersed in 60 mL of ethanol solution (ethanol: water 4:1, v / v). Then, ammonia water was added to the mixed solvent and the pH was adjusted to 8.5. Ultrasonication was performed for 10 min. After standing at 40 °C for 6 h, 135 mg of dopamine hydrochloride was added to the bottle and stirred at 500 rpm for 2 h. The obtained product was separated by an external magnetic field and washed with water and ethanol. Vacuum drying was performed at 60 °C for 7 h. Fe3O4@h-BN@PDA was obtained.
[0034] Example 4 Characterization of the above materials: 1. h-BN, Fe3O4 prepared in Comparative Example 1, Fe3O4@h-BN prepared in Example 1, Fe3O4@h-BN@SiO2 prepared in Comparative Example 2, and Fe3O4@h-BN@SiO2@PDA prepared in Example 1 were subjected to infrared detection, and their FT-IR images are shown in the attached figure. Figure 1 As shown. For Fe3O4@h-BN@SiO2@PDA, where Fe3O4 is at 580cm -1 There is a strong absorption peak at 1380 cm-1, which is caused by the stretching vibration of Fe-O; h-BN -1 and 803cm -1There are two broad absorption bands at 1080cm, corresponding to the in-plane stretching vibration and out-of-plane bending vibration of BN respectively; -1 The peak at corresponds to the stretching vibration of Si-O.
[0035] 2. The SEM images of the materials described in the examples of this application are shown in the attached Figure 2 As shown, a is h-BN; Figure b is Fe3O4@h-BN prepared in Example 1; Figure c is Fe3O4@h-BN@SiO2@PDA prepared in Example 1; SEM clearly shows the irregular morphology of the nanomaterials. Fe3O4@h-BN has more magnetic microspheres of Fe3O4 than h-BN, and the surface of Fe3O4@h-BN@SiO2@PDA is obviously rough, which shows that SiO2 and PDA are successfully attached to the surface of Fe3O4@h-BN.
[0036] 3. The Fe3O4@h-BN@SiO2@PDA prepared in Example 1 of the present application was analyzed by EDS energy spectrum, and its elemental composition analysis table is shown in Table 1. The elemental composition analysis shows that Fe3O4@h-BN@SiO2@PDA is composed of carbon (29.76% wt), nitrogen (25.27% wt), oxygen (26.00% wt), silicon (1.72% wt), iron (4.57% wt) and boron (12.67% wt). The silicon element and carbon element respectively prove the presence of SiO2 and PDA.
[0037] Table 1 In summary, the successful preparation of the material Fe3O4@h-BN@SiO2@PDA can be confirmed.
[0038] Effect Example 1 Weigh 10 mg of each drug in Table 2 and prepare a 100 µg / mL solution. Measure its absorbance with a UV-visible spectrophotometer. Weigh 10 mg of Fe3O4@h-BN@SiO2@PDA in a test tube, add 5 mL of drug solution, shake at 500 rpm for 10 min, perform magnetic separation with a magnet, and take the supernatant. Measure its absorbance with a UV-visible spectrophotometer, calculate its corresponding concentration C2, and calculate the adsorption amount Q of TC by the material in 3 parallel groups.
[0039] Q=(C1-C2)V / m Where C1 and C2 represent the concentration of the drug before and after adsorption (µg / mL), V represents the volume of the added drug (mL), and m represents the mass of the adsorbent material (mg). The selectivity of 30 common drugs was initially screened, and the results are shown in Table 2.
[0040] Table 2 Note: * indicates significant difference in adsorption amount compared with ciprofloxacin (p less than 0.05) It is demonstrated that the magnetic adsorbent containing h-BN described in the present application has high selective adsorption for quinolone antibiotics.
[0041] Effect Example 2 Quinolone antibiotic adsorption experiment Standard substances ciprofloxacin hydrochloride (CIP), lomefloxacin hydrochloride (LOM), levofloxacin hydrochloride (OFL), and enrofloxacin (ENR) were prepared into a mixed standard solution of quinolone antibiotics (containing 5 μg / mL ciprofloxacin, 5 μg / mL levofloxacin, 5 μg / mL lomefloxacin, and 5 μg / mL enrofloxacin).
[0042] 25 mg of Fe3O4@h-BN@SiO2@PDA was added to 5 mL of the mixed standard solution of quinolone antibiotics. After the sample solution was shaken at 500 rpm for 10 min, Fe3O4@h-BN@SiO2@PDA was collected from the solution with a magnet and the supernatant was discarded. Then, 0.5 mL of methanol-phosphoric acid solution (volume ratio of 95:5) was added to the tube and eluted at 800 rpm for 5 min. The elution was repeated 3 times and the eluate was combined. The eluate was concentrated using a vacuum centrifugal concentrator, re-dissolved with 0.5 mL of mobile phase, and injected into HPLC for detection. Three parallel experiments were performed, and the results are shown in Table 3.
[0043] Table 3 It is proved that the Fe3O4@h-BN@SiO2@PDA prepared in this application has a good adsorption effect on quinolone drugs.
[0044] Effect Example 3 Weigh 10 mg of ciprofloxacin and prepare a 100 µg / mL solution. Measure its absorbance with a UV-visible spectrophotometer. Weigh 10 mg of adsorbent in a test tube, add 5 mL of ciprofloxacin solution, and shake at 500 rpm for 10 min. If the material contains Fe3O4 components, separate the solid by magnetism. If the material does not contain Fe3O4 components, separate the solid by centrifugation and take the supernatant. Measure its absorbance with a UV-visible spectrophotometer and calculate its corresponding concentration C2. Repeat 3 groups to calculate the adsorption amount Q of the material on TC.
[0045] Q=(C1-C2)V / m In the formula, C1 and C2 represent the concentration of the drug before and after adsorption (µg / mL), respectively, V represents the volume of the added drug (mL), and m represents the mass of the adsorbent material (mg). Fe3O4 is prepared in Comparative Example 1, Fe3O4@h-BN and Fe3O4@h-BN@SiO2@PDA are prepared in Example 1, Fe3O4@h-BN@SiO2 is prepared in Comparative Example 2, Fe3O4@h-BN@PDA is prepared in Comparative Example 4, and Fe3O4@SiO2@PDA is prepared in Comparative Example 3. The results are shown in Table 4.
[0046] Table 4 This shows that the combined effect of SiO2, PDA and Fe3O4@h-BN improves the adsorption effect of the material on quinolone antibiotics.
[0047] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A magnetic adsorbent containing h-BN, characterized in that: It is prepared by the following steps: S1: Disperse h-BN and iron salt in water in turn, stir to dissolve the iron salt, add alkaline solution to adjust the pH to 10-11, and obtain a mixed solution; S2: stirring the mixed solution at 800-1000 rpm for 5-7 h at 80-90 °C, collecting the product with a magnet, washing, and drying to obtain a Fe3O4@h-BN composite material; S3: Disperse the Fe3O4@h-BN composite material in an ethanol solution, add an alkaline solution, adjust the pH to 8-8.5, drop tetraethoxysilane into the reaction system, react at 35-50 °C for 5-7 h, then add dopamine hydrochloride to the reaction system, stir at 400-500 rpm at room temperature for 1-3 h, separate the product with a magnet, wash and dry to obtain the magnetic adsorbent Fe3O4@h-BN@SiO2@PDA.
2. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: The iron salt is selected from ferrous chloride or ferrous sulfate; the alkaline solution is selected from ammonia water, sodium hydroxide solution or potassium hydroxide solution; and the ethanol solution is an ethanol solution with a volume ratio of ethanol to water of 4:
1.
3. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: The mass molar ratio of h-BN to iron in iron salt in S1 is 60 mg:0.8-1.2 mmol.
4. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: In the reaction system described in S3, the dosage relationship of Fe3O4@h-BN, tetraethoxysilane and dopamine hydrochloride is 150 mg: 0.2-0.3 mL: 120-150 mg.
5. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: The dosage relationship of h-BN and water in S1 is 150 mg:40-70 mL.
6. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: The dosage relationship of Fe3O4@h-BN and ethanol solution in S3 is 150 mg:40-70 mL.
7. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: The mass molar ratio of h-BN to iron in the iron salt in S1 is 60 mg:1 mmol; In the reaction system described in S3, the dosage of Fe3O4@h-BN, tetraethoxysilane and dopamine hydrochloride is 150 mg: 0.25 mL: 135 mg.
8. The magnetic adsorbent containing h-BN according to claim 1, characterized in that: The dosage relationship of h-BN and water in S1 is 150 mg:50 mL; The dosage relationship of Fe3O4@h-BN and ethanol solution in S3 is 150 mg:60 mL.
9. A method for preparing the magnetic adsorbent containing h-BN as claimed in any one of claims 1 to 8.
10. Use of the magnetic adsorbent containing h-BN as claimed in any one of claims 1 to 8 in the detection of quinolone antibiotics.
Citation Information
Patent Citations
Starch-based magnetic adsorbent as well as preparation method and application thereof
CN118743980A